Dealing with Sexual Discrimination and Violence in German Universities : An Inventory - Schüz, Hannah-Sophie; Pantelmann, Heike; Wälty, Tanja; Lawrenz, Nina (My University, 2022)
Sexual discrimination and violence can be found in all areas of society, and universities are not the exception. Often regarded as safe institutional spaces, universities are far from rid of these problems. This article shows how sexual violence has long been tabooed and normalized in the German university context, and how this is reflected in the ambivalent approach German universities have adopted on this issue. Based on an evaluation of the way universities address the problem on their websites, as well as on telephone interviews with university internal experts, we show and discuss the way these institutions handle the problem and their legal anchoring. The results help to identify relevant actors and practices, providing a starting point for the development of strategies for action so as to better address and combat sexual violence in universities.
Keywords: Gender equality polic; Gender relations; Institutionalization; Sexual discrimination; Sexual violence; University; ddc:300